News Writing and Reporting for Todays Media - Itule, Bruce D. and Anderson, Douglas A. (New York Random House, Inc., 1987)
We wrote News Writing and Reporting for Todays Media to show students what it is like to be a news reporter and writer. Our aim was to write an all-encompassing text and to make it lively. We wanted to make the drama of news reporting come alive, to kindle an excitement while painting a realistic picture.
Keywords: Business English